Doctor De Soto - Steig, William (New York : Scholastic Inc, 1982)
Doctor De Soto is so brave . . . but is it wise for a mouse to treat a fox?
A Newberry Honor Book
Keywords: Dentists-Stories; Dentists-Fiction